Toxic heavy metal ions contamination in the aqueous environment, its toxicity and methods of microbial remediation - Liu Liying; Hou Meiling; Yin Qiang; Liu Yinghao (Green Chemistry Letters and Reviews)
Heavy metal compounds are used in a variety of industrial processes, including tanning, chrome plating, anti-corrosion treatments, and wood preservation. Heavy metal ion pollution in water and wastewater is often caused by industrial effluent discharge into open water sources. Toxic heavy metal ions such as As (III), Cr (VI), Cd (II), and Pb (II) are well-known and enter the body through a variety of pathways, including the food chain, respiration, skin absorption, and drinking water. These heavy metal ions produce oxidative stress in cells, resulting in cell organelle destruction. Heavy metals produce toxicity and may cause genetic material mutation or change, histone modification, and epigenetic alteration at various stages. Furthermore, heavy metals are linked to heart failure, renal damage, liver failure, and a variety of skin problems. For heavy metals cleanup, several standard approaches are utilized. Nonetheless, these technologies are costly and result in toxic sludge after treatment. As a result, there is an urgent need for an appropriate, environmentally safe, and efficient heavy metal removal technology. For heavy metal removal, microbial-based approaches are regarded as both environmentally benign and cost-effective. This review focuses on heavy metal pollution in water, its harmful consequences, and heavy metal cleanup by microbiological means.